The Literary Sources and Historical Implications of Ephesians - Dickinson, A. J. (The biblical world, 1914)
The more we study Paul the more we see that Paulinism is the application of the gospel to human affairs. The letters of the apostles are not studied productions but are born of actual situations. Any attempt to make these letters more vivid and real is to be welcomed. Dr. Dickinson gives us an unconventional treatment and one that is sure to make men appreciate more fully the apostles' work.